Analisis faktor yang mempengaruhi keputusan pemilihan program studi spesialis radiologi kedokteran gigi - Chrisna Ardhya Medika; Rellyca Sola Gracea; Lusi Epsilawati; Azhari Azhari; Farina Pramanik (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This paper aims to determine the factors that influence the decision making of a general dentist to become a dentomaxillofacial radiologist, particularly in Indonesia. Material and Methods: This research used a descriptive design with survey techniques, and the research samples were residents of dentomaxillofacial radiology residency program and dentomaxillofacial radiologists in Indonesia. This research was conducted by the way respondents filled out questionnaires, based on the concept of marketing and purchasing on the expertise of dental radiology specialists. Results: There are variations in answers that are dominated by the value of product purchases as a dental radiology specialist is urgently needed. Conclusion: Dentomaxillofacial radiologist is a profession that is rarely found in Indonesia so it becomes a reliable job in the future as more experts are needed. The promotional activities of its residency program are still much of lack.